The work performance employees of the environmental service of south nias district was examined from the effect of work ethic and communication: Work Ethic; Communication; Work Performance; - Timotius Duha (Junal Ilmu Manajemen, 2023)
This study aims to determine the effect of work ethic and communication toward work performance of employees of the South Nias Regency Environmental Service. This research is a quantitative type with multiple linear regression analysis tools, the number of respondents is 34 employees. The type of data is primary data, and data collection uses a questionnaire method. The results of the regression test showed that partially the work ethic and communication, each partially had a positive and significant effect on work performance. Simultaneous testing shows that Work Ethic and Work Communication together have a Positive and Significant influence on Work Performance.